Church-in-a-box: making space sacred in a non-traditional setting. Issue 3 (2nd September 2017) - Finlayson, Caitlin
ABSTRACT: How are non-traditional sacred spaces experienced and sacralized? Non-traditional sacred sites offer a unique and useful perspective for exploring notions of sacralization, the process of making space sacred. This paper explores sacralization through an investigation of Unity of Fredericksburg, a non-traditional spiritual community that meets in an executive office building, using in-depth interviews with church leaders and members. These interview findings help shed light on how the process of sacralization occurs and suggest that it is the collective, emotional engagement with space that makes it sacred. Non-traditional houses of worship, though not imbued with conventional notions of "sacredness", serve as functionally sacred for believers and the transiency of their sacred qualities provides a useful foundation for geographers of religion to explore how the sacred is made and experienced.